Proceedings of the 2020 Genetic and Evolutionary Computation Conference 2020
DOI: 10.1145/3377930.3390193
|View full text |Cite
|
Sign up to set email alerts
|

Improving neuroevolutionary transfer learning of deep recurrent neural networks through network-aware adaptation

Abstract: This paper utilizes 12 ight logs each from aircraft of three dierent airframes: Cessna 172 Skyhawk (C172s), Piper-Archer 28 Cherokees (PA-28s) and Piper-Archer 44 Seminoles (PA-44s). These aircraft share 18 common sensor parameters, and then each has varying sensor parameters for their engine(s). The data les used in this work are freely available as comma separated value (CSV) format as part of the EXAMM github repository 4. The following table presents which sensors are present for which airframe and which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…while the other weights are copied from the parent. This network-aware approach using the statistical distribution of a network's weights has also been shown in other work to speed transfer learning, lending further credence to this approach (ElSaid et al 2020).…”
Section: Weight Initialization and Inheritancesupporting
confidence: 60%
“…while the other weights are copied from the parent. This network-aware approach using the statistical distribution of a network's weights has also been shown in other work to speed transfer learning, lending further credence to this approach (ElSaid et al 2020).…”
Section: Weight Initialization and Inheritancesupporting
confidence: 60%
“…The main objects of tourism security early warning system are tourists or local residents [ 15 , 16 ]. Therefore, the information it provides is more detailed, which has a good effect in the security of outbound tourism.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed work is utilizes components from the Evolutionary Exploration of Augmenting Memory Models (EXAMM) algorithm [31] as its core and utilizes its mutation, crossover and training operations in online scenarios. EXAMM is a distributed NE algorithm that evolves progressively larger RNNs for large-scale, multivariate, real-world TSF [14,15]. EXAMM evolves RNN architectures consisting of varying recurrent connections and memory cells through a series of mutation and crossover (reproduction) operations.…”
Section: Methodsmentioning
confidence: 99%
“…Generated offspring inherit their weights from their parents, which can significantly reduce the time needed for their training and evaluation [25]. It has been shown that EXAMM can swiftly adapt RNNs in transfer learning scenarios, even when the input and output data streams are changed [15] [14], which served as a preliminary motivation and justification for being able to adapt and evolve RNNs for TSF in online scenarios.…”
Section: Methodsmentioning
confidence: 99%